Chitosan Based Acetone Sensor For Detecting Low Concentration Acetone - Nasution, Tulus Ikhsan (2013)
Chitosan based acetone sensors (CBASs) which are capable of sensing the presence of acetone vapor in low concentration have been successfully fabricated including the combination of photolithograpy and electrodeposition techniques. The CBASs were fabricated in film form in which the chitosan used was synthesized from waste product of crab shells which was purchased from Sigma Aldrich. It was found that the amine and hydroxyl groups in molecular structure of chitosan film can interact well with the molecules of acetone vapor touching its surface. This interaction was indicated by different output voltages of CBAS for different concentration of acetone. The detection of low concentration acetone has been considered as an attractive area of study. Some medical reports express that the acetone concentration in the breath varies from 0.3 to 0.9 ppm in healthy people to more than 1.8 ppm for diabetics. This makes acetone a suitable chemical marker for diabetes diagnosis through exhaled breath. Therefore, the preliminary study on the laboratory testing of the CBAS electrical properties to acetone vapor-contaminated air in range of 0.1 – 100 ppm was carried out at room temperature (~25-30oC) in normal air. This aims to prove the great potential of CBAS as an application in diagnosing diabetes mellitus through breath exhaled by diabetics. The results showed that electrical response of CBAS increased very rapidly, in around 10 s, once its surface was exposed to both wet air and acetone vapor contaminated wet air. The sensors also exhibited quick recovery i.e., approximately less than 200 s once the exposure was removed and the reading dropped to its original values. As a result of exposure for 5 min, CBASs under 1.5 volts in supplied voltage yield maximum response values of approximately 3.9, 12.3, 40.5, 47, 66.4 and 70.2% when they are exposed to 0.1, 1, 10, 20, 50 and 100 ppm acetone vapor contaminated wet air, respectively. When the measurements were repeated continuously, the CBASs showed remarkably adequate repeatability. During testing, the CBASs operated in stable condition, indicated by no significant fluctuation in reading. Thus, the performance of the CBAS electrical properties achieved the requirements of a good sensor.